Exploring the work and non-work interface - Perrewe, Pamela L.; Ganster, Daniel C. (Emerald, 2007)
This is an annual research series devoted to the examination of occupational stress, health and well being, with particular emphasis on the multi-disciplinary nature of occupational stress. Titles pull together the various streams of research from a variety of disciplines to better capture the significant bodies of work in occupational stress and well being. A multidisciplinary and international perspective is provided to give a thorough and critical assessment of issues in occupational stress and well being. The theme for this volume is: exploring the work and non-work interface which discusses, amongst others, social anxiety, the importance of coping, working with family, women in the workplace and work addiction.
Keywords: Job stress.; elektronické knihy; electronic books